2019
DOI: 10.1249/mss.0000000000001970
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Impairment in Cardiopulmonary Fitness after Breast Cancer Chemotherapy

Abstract: Purpose Anthracycline chemotherapy (AC) is associated with acute reductions in cardiopulmonary fitness (V˙O2peak). We sought to determine whether changes in V˙O2peak and cardiac function persisted at 12 months post-AC completion, and whether changes in cardiac function explain the heightened long-term heart failure risk. Methods Women with breast cancer scheduled for AC (n = 28) who participated in a nonrandomized trial of exercise training (ET; n = 14)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…Several BC therapies can cause cardiovascular injury, including anthracycline chemotherapy, which is associated with a dose-dependent, progressive, myocardial injury [10]. Accordingly, impairments in peak VO 2 could be attributed to "central" limitations that reduce peak exercise cardiac output and left ventricular ejection fraction-the current clinical standard measure for detecting and monitoring cardiotoxicity [7,11,12]. However, "peripheral" impairments in exercise blood flow, citrate synthase activity, and relative reductions in oxidative muscle fiber and capillarity have been reported in individuals after systemic cancer therapy [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several BC therapies can cause cardiovascular injury, including anthracycline chemotherapy, which is associated with a dose-dependent, progressive, myocardial injury [10]. Accordingly, impairments in peak VO 2 could be attributed to "central" limitations that reduce peak exercise cardiac output and left ventricular ejection fraction-the current clinical standard measure for detecting and monitoring cardiotoxicity [7,11,12]. However, "peripheral" impairments in exercise blood flow, citrate synthase activity, and relative reductions in oxidative muscle fiber and capillarity have been reported in individuals after systemic cancer therapy [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, impairments in peak VO 2 could be attributed to "central" limitations that reduce peak exercise cardiac output and left ventricular ejection fraction-the current clinical standard measure for detecting and monitoring cardiotoxicity [7,11,12]. However, "peripheral" impairments in exercise blood flow, citrate synthase activity, and relative reductions in oxidative muscle fiber and capillarity have been reported in individuals after systemic cancer therapy [11,[13][14][15]. Abnormalities in skeletal muscle composition may also limit exercise tolerance; Reding et al reported peak VO 2 was inversely related to the ratio of intermuscular fat (IMF) to skeletal muscle (SM) within the paraspinal muscles in cancer survivors [16].…”
Section: Introductionmentioning
confidence: 99%
“…8 Chemotherapy and drug therapies have high toxicity and can damage organs such as liver or heart. 9 Depending on treatment course, this may leave to irreversible tissue damage. While cancer survivorship is growing, 10 so is cardiotoxicity.…”
mentioning
confidence: 99%
“…Specifically, this included a lower LVEF at peak exercise (153), or a lower cardiac index and SV index at peak exercise (152). Recent work from our laboratory has shed some light on the evolution of cardiac reserve impairment in breast cancer patients undergoing anthracycline chemotherapy using exCMR (154,155). In this series of studies, we found that exercise stroke volume tended to be lower shortly following anthracycline chemotherapy (P = 0.06) (155), however over the following 12-months this evolved into a blunted augmentation of LVEF and SV during exercise, resulting in a reduction in peak exercise CO (154).…”
Section: Adult Cancer Survivorsmentioning
confidence: 99%
“…Recent work from our laboratory has shed some light on the evolution of cardiac reserve impairment in breast cancer patients undergoing anthracycline chemotherapy using exCMR (154,155). In this series of studies, we found that exercise stroke volume tended to be lower shortly following anthracycline chemotherapy (P = 0.06) (155), however over the following 12-months this evolved into a blunted augmentation of LVEF and SV during exercise, resulting in a reduction in peak exercise CO (154). One of the more intriguing findings comes from a small (n = 48) prospective analysis of mixed adult and pediatric patients with advanced cancer undergoing high-dose anthracycline chemotherapy (156).…”
Section: Adult Cancer Survivorsmentioning
confidence: 99%